Estimating Evapotranspiration of Paddy Field and Teak Plantation Using Remote Sensing - Piyapong Tongdeenok; Samakkee Boonyawat; Kankhajane Chuchip (Agriculture and Natural Resources, 2007)
The objective of this study was to investigate suitable models that can estimate actual evapotranspiration (ETa) by using remote sensing data. To achieve this, the study compared evapotranspiration in a paddy field in Sukhothai with a teak plantation in Lampang using remotely sensed data. The investigation period covered two years and eight months from January 2002 to September 2004. 17 AVHRR images from NOAA/ satellite were used for the study. It was found that the relationship between ETa and remote sensing parameters such as normalized difference vegetation index (NDVI), land surface temperature (LST) and surface albedo (Sur_alb) of each site, were highly significant. The suitable model for each site and each period were as follows: in the paddy field for the whole period ETa = -1.21+ 0.73 (NDVI) + 0.19 (LST) + 4.02 (Sur_alb), r2 = 0.71, during rice planting season ETa = 3.99 + 0.83 (NDVI) + 0.01 (LST) +1.61(Sur_alb), r2 = 0.65 and after rice planting season ETa = -1.93 + 1.42 (NDVI) + 0.2 (LST) + 7.44 (Sur_alb), r2 = 0.85. The derived equation for the teak plantation was ETa = -2.87 + 0.18 (NDVI) + 0.27 (LST) + 0.57(Sur_alb): r2 = 0.4, rainy season ETa = 3.7 - 0.60 (NDVI) + 0.07 (LST) + 4.57 (Sur_alb) , r2 = 0.64. In addition, the best suited equation for the dry season was ETa = -4.23-0.0004(NDVI)+0.37(LST)-5.8 (Sur_alb), r2 = 0.60. It can be concluded that the remote sensing approach is applicable for ETa estimation. Advantages of using remote sensing are that it provides spatial distribution for large-areas and it is relatively easy to find out NDVI, surface albedo and surface temperature when compared to other measurement methods.